Healthy islands concept in Papua New Guinea - Sonia Yeung; Jeanette Selep (2016)
World Vision has adopted the Healthy Island Concept (HIC), a participatory community engagement, planning, and monitoring approach unique to the Pacific Islands. After more than one year of implementation, significant positive results can be seen, including communities succeeding in instigating hygiene behaviour change and adapting their lifestyle to achieve better health outcomes. Through community-embedded HIC Facilitators, communities formulate their collective vision of a “healthy community” and monitor the implementation of community plans. So far, successes include a high level of community ownership, participation and accountability as well as significant progress on activity implementation addressing hygiene and broader health issues in the target communities.